Increased Funding for AIDS-Engaged Faith-Based Organizations in Africa? - Olivier, Jill (Taylor and Francis, 2014)
While civil society organizations (CSOs) have been recognized as being critically import to the HIV/AIDS response by multilaterals, agencies, and governments, the extent to which they have been able to access targeted sources of funding remains a much-debated concern. There is evidence that funding for well-established CSOs has increased significantly over the last decade, but it has also been suggested that local-level and less formal CSOs still remain largely disconnected from donor funding streams and unaligned with national strategies. Concerns have been raised as to whether the substantial international funding provided for HIV/AIDS has indeed “trickled down” effectively to the local level—and how this may play out in the future, especially in the face of increasing resource constraints.